Analysis of schrines detection using geospatial techniques : case study of Lembah Bujang, Kedah, Malaysia - Shairatul Akma binti Roslan (Kulliyyah of Architecture and Environment Design, International Islamic University Malaysia, 2016)
Lembah Bujang is an oldest historical site dated back 2 million years ago and become a starting point to understand the origins and history of civilization in Malaysia. The aim for this research is to identify the potential shrines area in three study areas consist of Lembah Bujang, Sungai Batu, and Kg. Pengkalan Bujang which is using RADARSAT and GIS techniques in conserving the historical site. Satellite Remote Sensing application has been proved efficiently used in various archaeological studies. The multi-temporal images of RADARSAT-1 and RADARSAT-2 are used to identify and spot the shrines area surrounding of sites. The images of multi-temporal in 2003 and 2014 with single microwave frequency 5.3 GHz, in the C-Band; the wavelength of 5.6 cm were interpreted through a specific site to address the research questions. Two techniques in identifying potential shrines consist of Local Adaptive Filtering and Feature Extraction have been used and tested to the RADARSAT images of three selected study areas by using processing software of ENVI and ArcGIS. The finding shows that the Local Adaptive Filtering on GAMMA Map filter is one of the best techniques in identifying potential shrines area due to it's preserving the pixel values of the images after processing. While edge enhancement improves the appearances of the shrines images to more readily interpret by the researcher.This research also will contribute possible remote sensing techniques in monitoring any expansions of land use developments surrounding the shrines area simultaneously assist in making recommendations in land use planning guidelines for preservation and conservation in the heritage site.